Carcinogenicity of deoxycholate, a secondary bile acid - Bernstein, Carol (Springer-Verlag, 2011)
High dietary fat causes increased bile acid secretion into the gastrointestinal tract and is associated with colon cancer. Since the bile acid deoxycholic acid (DOC) is suggested to be important in colon cancer etiology, this study investigated whether DOC, at a high physiologic level, could be a colon carcinogen. Addition of 0.2% DOC for 8–10 months to the diet of 18 wild-type mice induced colonic tumors in 17 mice, including 10 with cancers. Addition of the antioxidant chlorogenic acid at 0.007% to the DOC-supplemented diet significantly reduced tumor formation. These results indicate that a high fat diet in humans, associated with increased risk of colon cancer, may have its carcinogenic potential mediated through the action of bile acids, and that some dietary anti-oxidants may ameliorate this carcinogenicity.